Greenland, Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
34-F-15 August 5, 1931. Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord]. East side along Yner [Ymer] Island, near Antarctic Sound. Photo taken from S. S. Veslekari.